From the 4Ps to the 4Es and a few other thoughts for the digital-age marketer - Sutherland, Rory (Henry Stewart Talks, 2009)
Thoughts for the digital-age marketer, A new medium, Utility applications, Talkability, The potency of channel preference -The importance of contextuality, A Google for mood, Twitter, Gentle persuasion is the most effective way, Less is cool, Acceptable ubiquity, Marketing is an equivalent form of investment, Building value with information, Advantages of digital advertising, John Mackey, Whole Foods
Archived at 2022/04/11